Right Ventricular Function in Acute Respiratory Distress Syndrome: Impact on Outcome, Respiratory Strategy and Use of Veno-Venous Extracorporeal Membrane Oxygenation - Petit, Matthieu; Jullien, Edouard; Vieillard-Baron, Antoine (Frontiers in Physiology, 2022)
ARDS remains a major public health problem with high mortality. Pulmonary vascular dysfunction is one of the pivot points of its pathophysiology, resulting in pulmonary hypertension (PH), higher levels of which are associated with mortality. PH develops as a result of endothelial dysfunction, pulmonary vascular occlusion, increased vascular tone, extrinsic vessel occlusion and vascular remodeling. This increase in right ventricular (RV) afterload causes uncoupling between the pulmonary circulation and the right ventricle which has no adaptive reserve mechanism other than dilatation, responsible for left ventricular compression, leading to circulatory failure. This state, also called severe acute cor pulmonale (ACP), is responsible for excess mortality. Strategies designed to protect the pulmonary circulation and the right ventricle should be the cornerstones of the care and support of patients with the severest disease, in order to improve prognosis, pending stronger evidence. ACP is associated with driving pressure ≥ 18 cmH2O, PaCO2 ≥ 48 mmHg and PaO2/FiO2 < 150 mmHg. RV protection should focus on these three preventable factors. Prone positioning, the setting of positive end-expiratory pressure and inhaled nitric oxide can also unload the right ventricle. When these strategies are insufficient, extracorporeal membrane oxygenation (ECMO), which improves decarboxylation and oxygenation and enables ultra-protective ventilation, should be discussed in seeking better control of RV afterload. This review reports the pathophysiology of PH in ARDS, describes RV function, and proposes an RV protective approach, ranging from ventilatory settings and prone positioning to inhaled nitric oxide and selection of patients potentially eligible for veno-venous ECMO.